2017
DOI: 10.1111/anu.12600
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary inulin and Jerusalem artichoke (Helianthus tuberosus) on intestinal microbiota community and morphology of Nile tilapia (Oreochromis niloticus) fingerlings

Abstract: This study investigated the effects of dietary inulin and Jerusalem artichoke (JA) on intestinal microbiota and morphometry of Nile tilapia fingerlings. Five treatment diets were designed to supplement inulin at 0 (basal diet), 2.5 and 5.0 g/kg, and JA at 5.0 and 10.0 g/kg. Nile tilapia larvae were fed experimental diets from the first feeding through the fingerling stage (84 days). The cultivation-dependent technique showed that dietary inulin at 5.0 g/kg and JA (at both levels) increased lactic acid bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…Although Clostridium was not observed in high proportions, other genera from the order Clostridiales contributed considerably to the milkfish gut microbiome with possibly similar biological functions, specifically Epulopiscium and Romboutsia . These taxa have been identified as prominent members of the gut microbiome in herbivorous and detritivorous fish exhibiting a symbiotic relationship with their host [ 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although Clostridium was not observed in high proportions, other genera from the order Clostridiales contributed considerably to the milkfish gut microbiome with possibly similar biological functions, specifically Epulopiscium and Romboutsia . These taxa have been identified as prominent members of the gut microbiome in herbivorous and detritivorous fish exhibiting a symbiotic relationship with their host [ 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bifidobacterium are commonly reported in the GI tract of endothermic animals, but they are only been isolated in few studies from the digestive tract of finfish (Merrifield et al, 2014 ). Recently, Boonanuntanasarn et al ( 2017 ) revealed increased population level of Bifidobacterium spp. by feeding Nile tilapia ( Oreochromis niloticus ) fingerlings fed inulin and Jerusalem artichoke ( Helianthus tuberosus ).…”
Section: Lactic Acid Bacteria (Lab) In the Gastrointestinal (Gi) Tracmentioning
confidence: 99%
“…Moreover diet supplementation with TPB alone significantly increased the regeneration process in the intestine of pigs. Boonanuntanasarn et al [46] investigated the effects of dietary supplementation with inulin and TPB on intestinal microbiota of Nile tilapia fingerlings. Nile tilapia larvae were fed for 12 weeks on experimental diets supplemented with inulin at as dose of 2.5 and 5.0 g/kg, and TPB at 5.0 and 10.0 g/kg from the first feeding.…”
Section: Tpb Studies In Animal Experimentsmentioning
confidence: 99%